PERSEPSI GURU DALAM MENGIMPLEMENTASIKAN KURIKULUM MERDEKA PADA SDN KAPUK 15 PAGI JAKARTA BARAT: JURNAL - Syamsul Arief; Yeni Nuraeni; Candra Puspita Rini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the implementation of the independent curriculum at the Kapuk 15 Pagi State Elementary School, West Jakarta and to determine the perceptions of elementary school teachers regarding the implementation of the independent curriculum at the Kapuk 15 Pagi State Elementary School. This research uses a qualitative approach with a descriptive type, namely the research used to examine natural objects that produce descriptive data. The research was carried out at Kapuk 15 am State Elementary School, West Jakarta. The data collection techniques used in this research are observation, interviews, documentation and questionnaires (as supporting instruments). Meanwhile, to analyze research data using data reduction techniques, data presentation, and drawing conclusions. To test the validity of the data using extended observations, increasing persistence using reference materials. Based on the research that has been carried out, it was found that the implementation of the independent curriculum at the Kapuk 15 am State Elementary School, West Jakarta has not been optimal because the teachers at Kapuk 15 am Elementary School are still learning how to implement it and still need special training regarding the independent curriculum. The implementation of the independent curriculum at SDN Kapuk 15 am is also still in the stage of implementing the independent curriculum, namely implementing the independent curriculum using an independent curriculum structure in developing its educational units, as well as applying the principles of the independent curriculum in implementing learning and assessment funds, and Elementary School Teachers' Perceptions Regarding Implementation The Merdeka Curriculum at the Kapuk 15 am State Elementary School is in the quite good category, this is proven by the results of interviews, and also the distribution of questionnaires which state that the independent curriculum makes it easier for teachers and students in the learning process, and creates a fun teaching and learning process.